Psychometric Properties of the Oldenburg Burnout Inventory in a Portuguese Sample of Aircraft Maintenance Technicians - Reis, Cátia; Tecedeiro, Miguel; Pellegrino, Pollyana; Paiva, Teresa; Marôco, João P. (Frontiers in Psychology, 2021)
From its initial conceptualization as emotional exhaustion, cynicism and reduced personal efficacy for the help professions, burnout has received increasing attention in modern times, especially after the 2019 WHO’s inclusion of this syndrome in the ICD-11 list. Burnout can be measured using several psychometric instruments that range in dimensionality, number of items, copyrighted and free use formats. Here we report the psychometric properties of data gathered with the Oldenburg Burnout Inventory (OLBI) in a sample of Portuguese Aircraft maintenance technicians. As far as we know this is the first study addressing the burnout syndrome in this occupational group. Data gathered with the OLBI displayed good evidence of validity related to internal structure, to other variables, with good evidence of reliability. We showed that burnout significantly correlated with mental and physical fatigue emphasizing the vital critical role that these variables play with safety in the aviation industry.